2013
DOI: 10.7567/jjap.52.052102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Using a Ag Anode with a Co-evaporation Thin Film of MoOx and α-Naphthyl Diamine Derivative in Organic Light-Emitting Diode

Abstract: We investigated the effects of using a Ag anode with the co-evaporation of molybdenum oxide (MoO x ) and N,N '-bis(1-naphthyl)-N,N '-diphenyl-1,1'-diphenyl-1,4'-diamine (α-NPD). The current density of the device with a Ag anode and a co-evaporation thin film was the highest among the various devices used owing to a low sheet resistance and charge transport. We discussed the mobility and carrier density of the co-evaporation thin film as compared with the electrical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…If the carrier mobility of the MoOx‐doped α‐NPD thin film is assumed to be 10 −4 m 2 V −1 s −1 , which is the same as the minimum mobility of band conduction, the carrier density must be 1.60 × 10 18 m −3 . This calculation showed that the carrier density of the MoOx‐doped α‐NPD thin film was much lower than that of a conventional organic semiconductor, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the carrier mobility of the MoOx‐doped α‐NPD thin film is assumed to be 10 −4 m 2 V −1 s −1 , which is the same as the minimum mobility of band conduction, the carrier density must be 1.60 × 10 18 m −3 . This calculation showed that the carrier density of the MoOx‐doped α‐NPD thin film was much lower than that of a conventional organic semiconductor, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…OLED technologies have undergone continuous development (1)(2)(3)(4). Tang et al reported the first efficient device with organic light-emitting material with a low-voltage below 10 V. This device consisted of a two-layer film of organic materials with a total thickness less than 150 nm (1).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, α-NPD was chosen as the HTL because its HOMO energy level (-5.42 eV) is suitable with that of the perovskite (-5.43 eV) (Figure 1d), it has a simple deposition process, and its hole mobility (1.17 x 10 ) [28], which is comparable to that of Spiro-OMeTAD [24].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously employed α-NPD as HTL for the fabrication of organic light emitting diode (OLED) [26][27][28] and inspired by the quest to fabricate efficient and low-cost PSCs, we studied the use of α-naphthyl diamine derivative of…”
Section: Introductionmentioning
confidence: 99%
“…copper phthalocyanine (CuPC), copper hexadecauorophthalocyanine (F16CuPC), 4,4 0 ,4 00 -trisfN, (3-methylphenyl)-N-phenylaminog-triphenylamine) (m-MTDATA), poly(ethylene-dioxythiophene):poly(styrene sulfonic acid) (PEDOT:PSS), conducting fluorocarbon coatings (CFx), self-assembled monolayer (SAM), tungsten trioxide(WO 3 ), molybdenum oxide (MoO x ) and Vanadium(V) oxide (V 2 O 5 ) are used as HIL to reduce the interfacial energy barrier between oxide electrode and hole-transport layer [1][2][3][4][5][6][7]. Van Slyke et al reported that highly stable organic light-emitting diodes (OLEDs) based on vapor-deposited Alq thin films had been achieved [1].…”
Section: Introductionmentioning
confidence: 99%